Stress fractures of the growth plates in the fingers of adolescent rock climbers Stressfrakturen der Wachstumsfugen der Finger jugendlicher Kletterer - Schöffl, Volker; Moser, Othmar; Küpper, Thomas (Die Unfallchirurgie, 2024)
Background: Primary periphyseal stress injuries (PPSI) of the hand and fingers are a rare condition overall but are most commonly seen in adolescent rock climbers and is the most common sport-specific injury in young climbers. Early diagnosis and treatment are crucial for a good treatment outcome and to avoid chronic sport-related injury. Objective: The aim of the study is to introduce the injury to a wider audience. Based on an analysis of the current literature, the pathophysiology is demonstrated and the diagnostic and treatment standards are analyzed. Prophylactic measures are also reported. Material and methods: Based on a systematic multiple database analysis, the current literature on PPSI of the hand and fingers in climbers were collected and further analyzed in a narrative review. The pathophysiology, diagnostic and treatment concepts are presented. Results: Most cases of PPSI to the hand and fingers are in young rock climbers; however, a few cases have been reported in gymnasts, baseball players and piano players. Overall, there are over 200 documented cases in the literature. Most are Salter-Harris III/Aitken II fractures but grade I, II and IV fractures have also been reported. Patients are mostly 13–15 years of age and within the main pubertal growth spurt. After diagnosis, usually by magnetic resonance imaging (MRI), treatment is often conservative, with an increasing number of cases requiring surgical revision. Surgery usually involves spot drilling of the growth plate to induce fusion. Discussion: Early diagnosis and treatment are critical for a good outcome. This includes specific education and information for athletes, coaches, parents and treating physicians. Also, the frequent use of the crimp position has also been shown to increase the risk of PPSI. Preventive aspects should target this as well as overall load management.
CRIS-Team Scopus Importer:2024-10-04
Keywords: Epiphyseal fracture; Finger fracture; Growth plate; Stress fracture; Transient fracture